Comparison of Fine Needle Aspiration Cytology and Histopathology in the diagnosis of lymph node pathologies at health facilities located in Hawassa: A 5-year retrospective study - Endeshaw Taye; Musa Mohammed Ali; Alemayehu Toma; Alemwosen Teklehaimanot (SAGE Open Medicine, 2022)
Objective: The aim of this study was to evaluate the performance of Fine Needle Aspiration Cytology in the diagnosis of lymph node pathologies in comparison with Histopathologic examination. Methods: A retrospective health facility-based cross-sectional study was carried out at health facilities located in Hawassa city among 101 patients who had both Fine Needle Aspiration Cytology and Histopathologic examination on the same site from 13 September 2016 to 30 August 2021. Background data were collected using a structured questionnaire and analyzed by SPSS version 20. Results: A total of 3892 patients had Fine Needle Aspiration Cytology for lymphadenopathies within a specified 5-year span, out of which 101 cases had both Fine Needle Aspiration Cytology and Histopathologic examination. The overall sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of fine needle aspiration cytology for the diagnosis of lymphoma were 88.2%, 92%, 91.8%, 88.5%, and 90.1%, respectively. Conclusions: Fine Needle Aspiration Cytology can be recommended for clinically significant lymphadenopathy as a first-line diagnostic test since it is fast, safe, cost-effective, reasonably sensitive, and specific with significant positive and negative predictive values and diagnostic accuracy.